1964
DOI: 10.1111/j.2042-7158.1964.tb07497.x
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids of Fagraea fragrans Roxb

Abstract: The major alkaloid of the leaves and fruits of Fagraea fragrans Roxb. has been isolated and shown to be 4-(2-hydroxyethyl)-5-vinyl nicotinic acid lactone identical with gentiamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1965
1965
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…The presence of alkaloids in the leaves of F. fragrans has been reported. 33 At the beginning of the flowering season (May-June), the percentage of alkaloids content in the leaves has been found to be highest (0.32%) and lowest (0.005%) after fruiting had occurred (October-November). The presence of 0.10% alkaloids has been reported from the ripe fruits.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The presence of alkaloids in the leaves of F. fragrans has been reported. 33 At the beginning of the flowering season (May-June), the percentage of alkaloids content in the leaves has been found to be highest (0.32%) and lowest (0.005%) after fruiting had occurred (October-November). The presence of 0.10% alkaloids has been reported from the ripe fruits.…”
Section: Resultsmentioning
confidence: 97%
“…The presence of 0.10% alkaloids has been reported from the ripe fruits. 33 An alkaloid gentianine has been isolated from the leaves and fruits of F. fragrans. 33 However, this alkaloid isolated from other species is reported to have various pharmacological activities including the potential anti-inflammatory effect on experimental animals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytochemical works were conducted on many parts of Fagraea Fragrans Roxb, Loganiaceae, such as isolated gentianine for antimalarial and antiamoebic from leaves, fruits, and twigs [1,2], and isolated fagraldehyde for antiplasmodial from bark and leaves [3]. The secondary metabolites of F. fragrans fruits have also mapped recently [4] and now we report three simple alkaloids from these fruits in order to boost our people and industries to use these for both medicinal and phytocosmetics.…”
Section: Introductionmentioning
confidence: 93%
“…Literature shows that little is known concerning the chemical composition of this species or its biological activities. Studies on other species of the genus Fagraea revealed diverse compound families such as alkaloids, secoiridoid glycosides, coumarins, flavanols, other phenols, and lignans in the stem bark, roots, and leaves [13][14][15][16][17][18][19][20][21]. The only chemistryrelated study on the fruits is of F. fragrans Roxb.…”
Section: Introductionmentioning
confidence: 99%